Eagle Syndrome with surgical removal of the calcified styloid process: A clinical case report (Research, Society and Development, 2021)
Eagle syndrome is a clinical condition associated with an increased styloid process, reaching more than 25mm in length, which generates a compression of crucial anatomical structures, causing neck and facial pain, dysphagia, otalgia, mouth opening limitation and other symptoms. Being a rare syndrome with symptoms similar to other pathological conditions, it is essential to implement the correct diagnosis and treatment. The treatment can be conservative or surgical by intraoral or extraoral approach. This study is a clinical case report, of a 40-year-old male subject, diagnosed with Eagle syndrome after presenting painful symptoms on mouth opening, dysphagia and otalgia and tomographic examination showing the styloid process with 30mm of length. The chosen treatment was surgical excision of the styloid process using the extra-oral approach, ensuring greater control of the great vessels, better exposure and less risk of bacterial contamination of the deep cervical spaces. As a result, the treatment was successful, with complete regression of symptoms without complications.